INTEGRASI METODE TAHFIDZ DALAM PENDIDIKAN KARAKTER: MEMBUMIKAN AL-QUR'AN DI TENGAH FENOMENA DEGRADASI MORAL REMAJA - Wina Susanti; Gusmirawati; Martin Kustati; Rezki Amelia (LPPM STAI Muhammadiyah Probolinggo, 2026)
The moral decline among adolescents in the digital age poses a serious challenge to Islamic education, necessitating an effective and sustainable character-building model. This study aims to analyze the integration of the Qur’an memorization method as a character-building tool for students aged 11–13 at the Fastabiqul Khairat Qur’an Memorization Center in Padang, West Sumatra. The study employs a qualitative approach with a case study design. Data were collected through six months of participant observation, in-depth interviews with nine informants, and analysis of supporting documents. Data analysis was conducted thematically to identify patterns and internal mechanisms of character formation through tahfidz activities. The results indicate that the practice of Al-Qur'an memorization significantly contributes to strengthening five key dimensions of character: honesty, discipline, responsibility, empathy, and emotional control. The findings reveal that the processes of repetition, interpretation, and internalization of Al-Qur'anic verses form a mechanism for the gradual and continuous internalization of values. Based on these findings, this study proposes two theoretical contributions: the Spiral Internalization concept, which explains the recursive process of character formation through the repetition of verses; and the Tahfidz-Character Nexus (TCN) construct, which identifies the relationship between tahfidz practice, the internalization of values, and character strengthening. These findings fill a gap in the literature regarding the internal mechanisms of character formation among early adolescent santri in the context of tahfidz education. Therefore, the TCN model and the Spiral Internalization mechanism have the potential to be developed as a pedagogical framework for strengthening Qur’an-based character education in the digital age.